A THE IMPLEMENTATION OF MAKE A MATCH TECHNIQUE IN STREET CHILDREN FOUNDATION (SCF) SIDOARJO USING FLANNEL EXPRESSION FOR INSTRUCTIONAL - Agustin Wahyu Fatmawati (STKIP PGRI SIDOARJO, 2022)
The objectives of this research was to find the result of implementation of make a match technique. The main purpose was to find out if students taught using the Make a Match technique would improve for vocabulary. The material given to the students was vocabulary in the context of a expression. Express your feeing was used for instructional media which is used to source of data. The subjects for the study was 4-6 grades in elementary school in SCF, Sidoarjo which had 20 students. The researcher used descriptive qualitative. The data for this research was collected from data of test for Each group. As a follow up from this research, it is suggested that English teachers should try using the Make a Match technique for teaching reading as an alternative to be applied in teaching reading in English. Key words: Teaching Vocabulary, Express your feeling, Make a Match Technique.